Mergers and Innovation Portfolios - José Luis Moraga-González; Evgenia Motchenkova; Saish Nevrekar (Tinbergen Institute, 2019)
This paper studies mergers in markets where firms invest in a portfolio of research projects of different profitability and social value. The portfolio nature of the investment problem brings about novel insights on the external effects of firmsâ exteuro™ investments. The investment of a firm in one project imposes a negative business-stealing externality on the rival firms because it lowers the probability they win the innovation contest for that project; however, the investment of a firm in one project also exerts a positive business-giving externality on the rival firms because it increases the likelihood they win the contest for the alternative project.
Keywords: O32; L13; L22; O31; 330; innovation portfolios; R&D contests; mergers